RACE AND MADNESS: LOCATING THE EXPERIENCES OF RACIALIZED PEOPLE WITH PSYCHIATRIC HISTORIES IN CANADA AND THE UNITED STATES - Kanani, Nadia (Critical Disability Discourses, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The intersectional social construction of race and madness has significantly shaped the lived experiences of racialized people with psychiatric histories. Unfortunately, there are few studies that consider the intersections between race and madness, and fewer still that locate these intersections within the social and political contexts of colonization, Canadian and American settler states, and immigration. The primary purpose of this article is to provide a review of the literature that looks at the intersections of race and madness in Canada and the US. In particular, the author will highlight common themes that are articulated in this literature. The second goal of this article is to locate the experiences of racialized people with psychiatric histories within the socio-historical context from which they arise. The author will argue that race and madness have been mutually socially constructed in Canadian and American society. Further, the author will illustrate that psychiatric constructions of racialized people have allowed for the rationalization and justification of both historical and ongoing colonial and imperialist domination, slavery, and exclusionary immigration policies.